2005
DOI: 10.1177/08857288050280010501
|View full text |Cite
|
Sign up to set email alerts
|

Academic Preparation of Adolescents With Disabilities for Postsecondary Education

Abstract: This study assesses the preparation of high school students with disabilities for postsecondary education. Transition planning information for 110 students from Grades 10 through 12 was reviewed. We found that (a) interest in attending postsecondary education declined from 77% to 47% over a 3-year period, (b) only four students had 4-year plans leading to postsecondary education, and (c) students were not enrolled in college preparatory classes or were transferred from college preparatory classes despite the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Furthermore, approximately one third of the youth with and without learning disabilities hoped to attain a college degree. Similarly, in their study of adolescents with a range of disabilities, Hitchings, Retish, and Horvath (2005) found that in 10th grade, 77% of their sample were interested in attending postsecondary education; however, the percentage of youth with this aspiration declined over time. It is clear from this previous research that a substantial proportion of youth with disabilities aspire to postsecondary education.…”
Section: Research On Educational Aspirationsmentioning
confidence: 94%
“…Furthermore, approximately one third of the youth with and without learning disabilities hoped to attain a college degree. Similarly, in their study of adolescents with a range of disabilities, Hitchings, Retish, and Horvath (2005) found that in 10th grade, 77% of their sample were interested in attending postsecondary education; however, the percentage of youth with this aspiration declined over time. It is clear from this previous research that a substantial proportion of youth with disabilities aspire to postsecondary education.…”
Section: Research On Educational Aspirationsmentioning
confidence: 94%
“…They found that academic achievement was identified by their participants to be the obstacle. Although the importance of improving academic achievement to facilitate the movement from high school to post-high school for students with disabilities is mandated by IDEA (Public Law 108-446 2004), students with disabilities are not academically well prepared for postsecondary education by their schools (Hitchings et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers are concerned that transition services are inadequate. For example, Hitchings, Retish, and Horvath (2005) investigated 110 secondary students with disabilities, of which, 77% expressed interest in attending college while in the 10th grade. After 3 years, interest in college dropped to 47%, only 4 students had 4-year transition plans for college, and most students had not taken college preparatory classes (Hitchings et al, 2005).…”
Section: Discussionmentioning
confidence: 99%